(untitled) (Tribhuvan University Journal, 2017)
Marriage is an important personal and social affair. A qualitative research was conducted to study attitude of present generation towards marriage. Sample size was 51. There was the use of triangulation of data and methods. When the study was carried out first, the qualitative data were collected by in-depth interview and analyzed manually in the interpretive-thematic analysis framework. Data saturated after 16 persons of marriageable age, those between 18 and 35, were interviewed. Some were interviewed twice or thrice. After five years, survey questionnaire was given to 35 individuals of marriageable age who were between 19 and 24. It consisted of five open-ended questions. Both samples comprised of the men and women living in Kathmandu valley at the time of research. Non-random convenience sampling method was used. Some themes were identified on why people marry. For current generation, marriage is needed for support, company, fulfillment of sex motive and conscious or unconscious social pressure. It was found that present generation perceives that parent generation married to continue customs, to obey parental orders and to settle permanently meaning to start a new family by bearing children. Race continuity is the common theme seen on both generations. The intention, beliefs and feelings of participants about marriage have been inquired to know the conative, cognitive and affective components of attitude.